Leader Analysis, Leadership, Myths, Attributes and Types of Leaders - Sholekhudin; Nikka Ayu Puspa; Eti Rusmalawati; Tamsikudin; Masduki Duryat (al-Afkar, Journal For Islamic Studies, 2025)
Leadership can be defined as behavior that has a specific purpose by influencing the activities of members and/or groups in order to achieve common goals that are designed to benefit the individual, group and organization. Leadership is the process of influencing other people both within the organization and outside the organization to take action to realize planned goals. Then there are 3 Leader Myths: DThe Birthright Myth, The For – All – Seasons Myth, The Intensity Myth. There are five attributes of leaders. Types of leaders There are 4 types of leaders.